Increased periprosthetic hip and knee infection projected from 2014 to 2035 in Taiwan. Issue 11 (November 2020) - Chang, Chih-Hsiang; Lee, Sheng-Hsun; Lin, Yu-Chih; Wang, Yi-Chun; Chang, Chee-Jen; Hsieh, Pang-Hsin
Abstract: Background: Periprosthetic joint infection (PJI) is a disastrous complication associated with hip and knee arthroplasty. The literature suggests that the economic consequences associated with treating PJI are substantial. Our study aimed to investigate the past trends of PJI rates, and to estimate the projected number of PJI cases, consequent bed-day requirements, and medical expenses in Taiwan up to year 2035. Methods: A nationwide epidemiological study was conducted using the inpatient database of the Bureau of National Health Insurance from 2004 through 2013. Patients with the International Classification of Disease-Clinical Modification, ninth revision (ICD9-CM) code 99, 666 (PJI) who had received surgical treatment including debridement, removal of hip or knee prosthesis, or revision of total hip/knee arthroplasty (THA/TKA) were identified. Projections were performed with Poisson regression on historical incidence rates in combination with projections of arthroplasty numbers from 2014 to 2035. Results: A total of 4935 hip (1871) and knee (3064) PJIs were identified between 2004 and 2013. The rates of PJI were 2.46% for hip arthroplasty and 1.63% for knee arthroplasty. The number of PJIs was expected to increase markedly with time from 728 in 2013 to 3542 in 2035 (a 4.87-fold increase). The bed-day requirements for treating PJI was 17, 205 in 2013 and is expected to be 82, 509 bed-days in 2035 (a 4.79-fold increase). The total hospitalization cost will increase 4.86-fold by 2035. Conclusions: The number of PJI cases is increasing rapidly due to the increasing numbers of arthroplasty surgery and the cumulative number of latent infection. This may place a large economic burden on the health care system.